Spatial distribution and source tracing of per- and polyfluoroalkyl substances (PFASs) in surface water in Northern Europe. (January 2017) - Nguyen, Minh A.; Wiberg, Karin; Ribeli, Erik; Josefsson, Sarah; Futter, Martyn; Gustavsson, Jakob; Ahrens, Lutz
Abstract: The impact of point and diffuse sources for 26 per- and polyfluoroalkyl substances (PFASs) in northern Europe were investigated by studying Swedish rivers ( n  = 40) and recipient seawater (Baltic Sea and Kattegat; n  = 18). Different composition profiles were observed in the rivers, with ten rivers having a remarkably high fraction of perfluoroalkane sulfonic acids (PFSAs; 65% of the ƩPFASs) as compared to other rivers (19%) suggesting major impact of one or several source types dominated by PFSAs. Population density and low latitude (south) were strongly correlated to the widely used perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA) as well as to perfluorohexanesulfonic acid (PFHxS). Significant relationships between several PFCAs and PFSAs (i.e. perfluorobutanoic acid (PFBA), perfluoroheptanoic acid (PFHpA), PFOA, perfluorobutanesulfonic acid (PFBS), and PFHxS) and dissolved organic carbon (DOC) were detected ( p  < 0.05), indicating chemical binding and co-transport with DOC in fresh water and seawater. Partial least squares regression analysis showed that perfluoroalkyl carboxylic acids (PFCAs) were related to latitude according to their perfluorocarbon chain length (C3, C7, C8, C9, C10 and C11 ), with longer chains associated with higher latitudes. This suggests the presence of mechanisms promoting higher prevalence of longer chained PFCAs in the north, e.g. precursor degradation, and/or aerosol associated stabilization of PFCAs and their precursors. Graphical abstract: Highlights: Point and diffuse sources showed specific PFAS patterns in rivers. Total riverine input of ΣPFASs into the Baltic Sea/Kattegat was 1170 kg yr −1 . PFCA levels were related to latitude according to their perfluorocarbon chain length. Significant relationship was observed between several PFASs and DOC ( p  < 0.05).